Ativação da solução irrigadora em endodontia: tendências de uso no Brasil e a influência sobre a resistência de união de um cimento biocerâmico - Buligon, Mônica Pagliarini (2024)
The present thesis investigated the application of irrigant activation methods and their potential advantages in endodontic treatment through a cross-sectional observational study and an in vitro study. In the first study (Article 1), the utilization of irrigant activation techniques among Brazilian endodontists were evaluated. Participants received an electronic questionnaire consisting of 16 questions covering sociodemographic and professional characteristics, along with inquiries regarding irrigation protocols and irrigant activation. A total of 282 valid responses were collected from June 2022 till October 2023. Data were analyzed descriptively and using the chi-square test (α=0.05). Most participants were female (61.3%), with an average of 14.5 years since dental school graduation and 10.2 years since endodontic specialized training. The respondents primarily resided in the South (49.6%) and Southeast (32.3%) regions, with the majority (44.3%) exclusively working in private practices. Sodium hypochlorite (75.9%) and EDTA (92.9%) were the most mentioned irrigating solutions during chemomechanical preparation. Among the reasons for selecting the irrigant, antimicrobial capability was considered the most important. Meanwhile, cleaning isthmuses and ramifications was the primary reason for using activation methods. Additionally, 78.3% reported always using some form of activation. Passive ultrasonic irrigation was the most popular technique, followed by the Easy Clean instrument. Only the workplace significantly influenced the activation technique usage (P<0.01). In the second study (Article 2), the objective was to analyze the influence of different irrigating solutions used in the smear layer removal (EDTA, peracetic acid, and saline solution), whether activated or not, on the bond strength of a calcium silicate-based endodontic sealer. Ninety single-rooted human teeth were randomly distributed into 6 experimental groups (n=15) according to the final irrigation protocol. In the non-activated groups, the canals were flooded for 5 minutes to allow the action of the respective irrigant. In the activated groups, the irrigating solutions were agitated using the Easy Clean instrument. Subsequently, the root canals were filled with AH Plus Bioceramic Sealer using the single-cone technique. The roots were transversely sectioned into 1.5-mmthick slices (± 0.3 mm), and the push-out test was conducted. These slices were then examined under a stereomicroscope to determine the failure pattern. When comparing the non-activated groups, peracetic acid showed higher bond strength values than EDTA and saline solution. Among the activated groups, EDTA yielded superior results to saline solution. Considering the same irrigant, there was no difference between the activated and non-activated groups. Most samples exhibited mixed failure. In summary, the findings of this thesis contribute to a better understanding of the utilization and importance of irrigant activation techniques in endodontic practice.